Shipping living donor kidneys and transplant recipient outcomes. Issue 3 (18th December 2017) - Treat, Eric; Chow, Eric K. H.; Peipert, John D.; Waterman, Amy; Kwan, Lorna; Massie, Allan B.; Thomas, Alvin G.; Bowring, Mary Grace; Leeser, David; Flechner, Stuart; Melcher, Marc L.; Kapur, Sandip; et al.
Abstract : Kidney paired donation (KPD) is an important tool to facilitate living donor kidney transplantation (LDKT). Concerns remain over prolonged cold ischemia times (CIT) associated with shipping kidneys long distances through KPD. We examined the association between CIT and delayed graft function (DGF), allograft survival, and patient survival for 1267 shipped and 205 nonshipped/internal KPD LDKTs facilitated by the National Kidney Registry in the United States from 2008 to 2015, compared to 4800 unrelated, nonshipped, non‐KPD LDKTs. Shipped KPD recipients had a median CIT of 9.3 hours (range = 0.25‐23.9 hours), compared to 1.0 hour for internal KPD transplants and 0.93 hours for non‐KPD LDKTs. Each hour of CIT was associated with a 5% increased odds of DGF (adjusted odds ratio: 1.05, 95% confidence interval [CI], 1.02‐1.09, P  < .01). However, there was not a significant association between CIT and all‐cause graft failure (adjusted hazard ratio [aHR]: 1.01, 95% CI: 0.98‐1.04, P  = .4), death‐censored graft failure ( [aHR]: 1.02, 95% CI, 0.98‐1.06, P  = .4), or mortality (aHR 1.00, 95% CI, 0.96‐1.04, P  > .9). This study of KPD‐facilitated LDKTs found no evidence that long CIT is a concern for reduced graft or patient survival. Studies with longer follow‐up are needed to refine our understanding of the safety of shipping donor kidneys through KPD. Abstract : This study examines the impact of shipping living donor kidneys with long cold ischemia time as part of a kidney paired exchange and finds no significant impact on the graft or patient survival.